A self-healing hydrogel with pressure sensitive photoluminescence for remote force measurement and healing assessment. Issue 4 (29th January 2019) - Li, Ming; Li, Weijun; Cai, Wei; Zhang, Xiaojie; Wang, Zhihang; Street, Jason; Ong, Wee-Jun; Xia, Zhenhai; Xu, Quan
Abstract : A self-healing hydrogel with a triple network structure and pressure sensitive photoluminescence for remote force measurement and healing assessment was successfully fabricated. Abstract : Light-guiding materials capable of total internal reflection, remote mechanical force sensing and self-healing are appealing in emerging fields including robotics and optical force measuring instruments. However, achieving all these features in a single material remains challenging at present. Herein, we have fabricated a fluorescence-responsive self-healing hydrogel with a triple network structure, which exhibits a 100% recovery in tensile strength after healing in air for 30 s and a 90% recovery in tensile strength after healing in water for 60 s. Furthermore, this material can resist a rotation of 1800° without breaking at the healed site. As the fluorescence excitation intensity of the hydrogel shows a good correspondence with the forces exerted on the hydrogel, the forces and the self-healing efficiency could be determined by measuring the intensity of the excitation peak. The stress states of the hydrogel in different liquids could be remotely monitored, eliminating the effect of surface contacts. With these sensing and self-healing abilities all in one, self-healing luminescent materials could be applied to tissue engineering, photoresponsive biosensors, flexible light guiding devices, structural health monitoring, etc.